Collaborative Governance Model in the Development Center of Economic Empowerment and Community Creativity in Bandung City - Aswin Aswin; Andre Ariesmansyah; Mona Indrianie (PT FORMOSA CENDEKIA GLOBAL, 2022)
The development of the creative economy industry in addition to the national sphere needs to also be accompanied by strengthening in regions in Indonesia which are considered to actually know their true potential to be used as opportunities by local governments so that they can contribute to the amount of national economic income. As one of the areas in Indonesia which is located in the province of West Java, namely the city of Bandung. The city of Bandung has been known as a Creative City because there are many creative economic actors developing in all production sectors such as culinary, tourist destinations, music, fashion, etc. which have very high added value so that they are able to compete in local and foreign markets. The role of multi stakeholders to implement the main program or policy to realize the goals of Collaborative Governance among 30 sub-districts throughout the city of Bandung which is connected to the direction of the policy of the City of Bandung which is collaborated on an ongoing basis accompanied by a series of norms, principles, and rules in decision making with the private sector, elements of the community, small and medium business actors towards the industrial sector at a macro level